JUNOS for dummies - Bushong, Michael (--For dummies., 2008)
If you're in charge of a network, you're probably aware that the only time anyone notices the network is when it goes down. With JUNOS software and JUNOS For Dummies, a friendly book to help you set it up and manage the software, you might be able to start convincing your clients to believe in magic. Here's the help you need for switching, routing, security, interface configuration, and more. Now, you can go inside JUNOS software and understand everything you need to know about operating a network with JUNOS. You'll learn how the control plane handles packet delivery and establishes traffic po.